The Effect of Brand Image and Brand Experience on Brand Satisfaction and Brand Loyalty of Wardah Cosmetics - Siti Nur Rahmadhany; Lia Amalia (PT FORMOSA CENDEKIA GLOBAL, 2023)
With the development of the world of cosmetics, everyone cannot be separated from cosmetics both for the face and body from morning to night. This study aims to determine the influence of brand image and brand experience on brand satisfaction and brand loyalty. In this study, the population studied was consumers who had used wardah at least 3 times in the Kebon Jeruk area. The sample in this study amounted to 200 people using the Lisler Structual Equation Model (SEM) method. Based on the results of the study shows that brand image has a positive effect on brand satisfaction. Brand experience positively affects brand loyalty. Brand experience has no effect on brand satisfaction. Brand image has no effect on brand loyalty. Brand satisfaction has no effect on brand loyalty